The Effect of Local Revenue on Capital Expenditure - Jouzar Farouq Ishak (Monex: Journal of Accounting Research, 2022)
This study examines the effect of local revenue, through local own-source revenue, balance fund, and other lawful local revenue, on capital expenditure. The method used is multiple regression and the data was collected from all provincial government in Indonesia. The regression result support all hypotheses. The findings of this study suggest that it is important for the provincial government to focus on increasing local own-source revenue and other lawful local revenue as this is the key success. Therefore, local government is needed by main government. This study implies that balanced fund from the central government affect expenditure for the provincial government.